Akhania, a new genus for Salsola daghestanica, Caroxylon canescens and C. carpathum (Salsoloideae, Chenopodiaceae, Amaranthaceae) - Sukhorukov, Alexander P.; Fedorova, Alina V.; Kushunina, Maria A.; Mavrodiev, Evgeny V. (PhytoKeys)
Genus Salsola s.l. was recently split into several genera of different phylogenetic placements within Salsoloideae, but both taxonomic and phylogenetic relationships of some parts of the former broadly defined Salsola still need to be clarified. A remarkable example is Salsola canescens nom. illegit. equivalent to Salsola boissieri, a taxon with tricky taxonomic history that was only recently transferred to the genus Caroxylon (tribe Caroxyleae). Salsola daghestanica, a narrow endemic of Central Dagestan (Russian Federation), was not even included in previous molecular studies of Salsoloideae and therefore still lacks an appropriate estimation of its relationships. Molecular phylogeny constructed here using nuclear and plastid DNA sequence data clearly placed Salsola daghestanica and Caroxylon carpathum as sister taxa and the clade S. daghestanica, Caroxylon canescens (Salsola boissieri), C. carpathum (Salsola carpatha) as a sister of the monophyletic Caroxylon. All three species are distinct from Caroxylon from a morphological standpoint. In conclusion, a new genus, Akhania, was established for these taxa. The detailed distribution of Akhania daghestanica is presented for the first time.